Modelagem, simulação e controle de uma nova proposta de aeronave tricóptero tilt-wing-coaxial-rotor - Arroyo, Alvaro Daniel Herrera (2021)
In the last decade, with the continuous development of Drones or Unmanned Aerial Vehicles (UAVs), a wide variety of models were tested and created, highlighting two types of Drones: multicopters and fixed wings. However, recently, there has been a growing demand to explore the “mixture” between these two types of vehicles. Leading to Vertical Take Off and Landing (VTOL) models, which seek to produce an aircraft capable of having the stability characteristics of a multicopter in hover flight mode, and the speed and high flight time that a fixed wing typically provides in cruise mode (straight level flight). In contrast to the advantages of VTOLs, the challenge with this class of aircraft is that they are subject to a high degree of non-linearity, typical of the mixture between two different aircraft architectures. Additionally, like all air vehicles, they must be able to deal with aerodynamic disturbances in the air. The main objective of this work is to propose a new UAV VTOL architecture with tricopter topology. This aircraft has independent rotor inclination together with wings, vectoring propulsion forces and aerodynamic forces, in order to help control the aircraft, reduce the downwash impact and take advantage of the same rotor structure to exert vehicle movement in several directions. The vehicle uses coaxial-rotors to balance the induced torque between the rotors for every tilting angle and, additionally, to increase the thrust force. The dynamic modeling was developed based on the physical laws that govern the propulsive, aerodynamic and inertial principles. Especially highlighting the mobile center of gravity (CG) due to the fact that the vehicle is characterized as a multi-body system, capable of assuming a non-symmetrical morphology. The aircraft design was made using SolidWorks® 3D design software, considering real electrical and mechanical components in order to obtain a theoretical model of the aircraft as close to reality. The vehicle's inertia tensor was validated by comparing the inertia tensor generated by the mathematical model and the inertia tensor generated by SolidWorks®. For the simulation, the aircraft model was linearized under the hover and cruise flight conditions and the aircraft control was implemented through a cascade control strategy. A state-integrated linear quadratic regulator controller (LQRI) was used to control the linear and angular velocities of the aircraft, while a proportional derivative integral controller (PID) was used to control the aircraft's position and attitude in space. The control strategy adopted allowed for the tracking of trajectories in a satisfactory manner, even in the presence of aerodynamic disturbances.